Application of advanced nanoclay material as a chemical fertiliser loss control agent for loss control fertiliser development in Thailand - J. Techarang (2018)
Copyright © 2017 Inderscience Enterprises Ltd. In development of novel chemical fertiliser loss control techniques for promoting agriculture, nanomaterials and nanotechnology have been involved in applications. In this study a type of natural nanoclay material, attapulgite, was applied after electron beam treatment of the as-mined material as a chemical fertiliser loss control agent (LCA). The LCA was mixed with normal chemical fertiliser to form loss control fertiliser (LCF). The LCF was applied to Thai rice growing in a farm field. In the aqueous phase, LCF self-assembled to form 3D micro/nano networks. The fertiliser could form fibrous crystals with the clay rods as the nucleus, obtaining a higher nitrogen spatial scale, so that the nutrient could be retained by the soil filtering layer, and thus nitrogen loss was reduced. Two types of LCFs, machine-made and manmade, were applied. After the LCF was applied, the growth and crop yield of the rice were studied and compared with that obtained with normal fertiliser, and the pH, N and K in soil were measured and analysed. On the control of releasing nitrogen, the two LCFs played some roles compared with the fertiliser control, particularly for some varieties, and the machine-made LCF performed better. On the control of the soil pH to be not too acidic, the manmade LCF performed better but was variety dependent. On the control of releasing K, a comparison showed that the manmade LCF was better than the machine-made LCF. The differences in the LCF behaviour should be correlated with the LCF structure which was due to how they were made.